Observation of t¯tH Production; Physical Review Letters; Vol. 120, iss. 23 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2018, 2018)
Title screen